IMPLEMENTASI PROGRAM KELUARGA BERENCANA PRIA DI KELURAHAN SRONDOL WETAN, KECAMATAN BANYUMANIK, KOTA SEMARANG (STUDI KASUS PENGGUNAAN MEDIS OPERASI PRIA DALAM PROGRAM KELUARGA BERENCANA PRIA) - Aryan Prasetyawan; Zaenal Hidayat; Nina Widowati (Journal of Public Policy and Management Review, 2013)
Research aims to describe implementation family planning man in kelurahan srondol wetan, sub-district banyumanik, city semarang and to know factors can obstruct familyplanning man in kelurahan srondol wetan. Locus used in this research is in kelurahan srondol wetan, sub-district banyumanik, city semarang. This research using methodsresearch qualitative spatially descriptive. Subject in this research consisting of 3 informer main.Based on the findings research shows that the family planning program man in kelurahan srondol wetan sub-districts banyumanik can be categorized less successful. The family planning program man can retard diponegoro is: ( social, environmental factorsreligion, culture ) factor resources, the communication and the target groups.Conclusion in this research is the implementation of the family planning program man in kelurahan srondol wetan sub-district banyumanik, less successful especially seen on the participation of the man who continue to decline. Based on the conclusions researchers recommend to the government to be more prioritize famliy planning program for man so that the program could achieve a more satisfactory results.